Migration as Foundation: Hagar, the 'Resident Alien', as Euro-America's Surrogate Self *. - Sherwood, Yvonne (Biblical Interpretation, 2018)
In this paper I use Hagar as a type of the shifting modern figure of the migrant, refugee or 'resident alien' inside the national family. In a modern update of the productively anachronistic typologies attempted by the Church Fathers, I use the presence of the Egyptian slave in biblical-European foundations to trouble the unstable concept of Europe/Christendom founded on a (distant) Christian heritage. I also use what I'm calling the 'Hagaramic' to disturb bland invocations of the 'Abrahamic' on the contemporary political stage. What happens when we replace the spiritualised, fraternal/paternal figure of the Abrahamic with the Hagaramic: the immigrant mimic of the Abrahamic; the resident female Egyptian alien who is there before, and supports and enables, the 'true' family? How does my attempt to use this figure relate to earlier attempts (by thinkers like Sigmund Freud or Edward Said) to draw on strange old biblical figures to force European identities outside themselves?